Microsoft visual C# 2005 express edition programming for the absolute beginner - Bakharia, Aneesha (Thomson, 2006)
Microsoft Visual C# 2005 Express Edition Programming for the Absolute Beginner provides beginner programmers with programming instruction using Visual C# 2005 Express Edition as a foundation language. Written for the entry-level, non-professional programmer, the book assumes no prior programming or scripting experience. Written in a straight-forward style, using a games-based approach that makes learning beginning-level programming fun and easy, Microsoft Visual C# 2005 Express Edition Programming for the Absolute Beginner is the perfect introductory programming book.